From pomegranate peels waste to one-step alkaline carbonate activated carbons. Prospect as sustainable adsorbent for the renewable energy production. Issue 1 (February 2022) - Saadi, W.; Rodríguez-Sánchez, S.; Ruiz, B.; Najar-Souissi, S.; Ouederni, A.; Fuente, E.
Abstract: Green and Sustainable activated carbons were obtained by one-step alkaline chemical activation process using a food industry lignocellulosic waste (pomegranate peels) as precursor. A non-harmful activating agent (alkali carbonate) was used, a more sustainable alternative to alkali hydroxides. The pomegranate peels-based activated carbons present high carbon content (>94%), low ash content (<0.5%) and significant nitrogen content (>1.0%); this last value is important because they can be highly effective CO2 adsorbents with the aim of improving biogas for renewable energy production. The activated carbons obtained were essentially microporous materials (micropore volume >82%), with BET specific surface area up to 1860 m 2 /g and total pore volume up to 0.879 cm 3 /g. These adsorbents were very efficient materials to retain CO2 at high pressure with an adsorption capacity similar or superior to experimental and commercial activated carbons. The CO2 adsorption capacity increased mainly with increasing activation temperature, the highest value being 717 mg/g at 3 MPa and 25 °C. Ultramicropores were very efficient in the CO2 and CH4 adsorption at low pressure while large micropores and small mesopores governed the high-pressure sorption behavior. These materials had negligible H2 adsorption capacity which makes them useful for separating gas mixtures in order to obtain pure H2 . Graphical Abstract: ga1 Highlights: Valorization of industrial pomegranate peels waste as activated carbons precursor. Sustainable single-step chemical activation with K2 CO3 to obtain activated carbons. Microporous Activated carbons (SBET up to 1860 m 2 ∙g −1 and VTOT up to 0.879 cm 3 ∙g −1 ). Useful adsorbents with high adsorption capacity and selectivity to CO2 (717 mg∙g −1 ). The activated carbons can be used for biogas upgrading in waste-to-energy scenario.